2009
DOI: 10.1373/clinchem.2008.108670
|View full text |Cite
|
Sign up to set email alerts
|

Oral Fluid Testing for Drugs of Abuse

Abstract: BACKGROUND Oral fluid (OF) is an exciting alternative matrix for monitoring drugs of abuse in workplace, clinical toxicology, criminal justice, and driving under the influence of drugs (DUID) programs. During the last 5 years, scientific and technological advances in OF collection, point-of-collection testing devices, and screening and confirmation methods were achieved. Guidelines were proposed for workplace OF testing by the Substance Abuse and Mental Health Services Administration, DUID testing by the Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
233
0
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(245 citation statements)
references
References 117 publications
0
233
0
12
Order By: Relevance
“…Several studies have shown a strong correlation between cocaine concentration in oral fluid and in plasma, proving oral fluid to be an appropriate sample matrix for the detection of drug use [34,35]. Due to its rapid elimination, with a half-life of only 3 h, the detection of cocaine in oral fluid is a suitable indicator of recent drug use close to the time of sampling [36].…”
Section: Application Of the Ceia For The Analysis Of Latent Fingermarksmentioning
confidence: 99%
“…Several studies have shown a strong correlation between cocaine concentration in oral fluid and in plasma, proving oral fluid to be an appropriate sample matrix for the detection of drug use [34,35]. Due to its rapid elimination, with a half-life of only 3 h, the detection of cocaine in oral fluid is a suitable indicator of recent drug use close to the time of sampling [36].…”
Section: Application Of the Ceia For The Analysis Of Latent Fingermarksmentioning
confidence: 99%
“…Risk of transmissible infection is much less than blood testing and there is evidence that oral fluid is more likely to show recent drug exposure [63]. With increasing incidence of driving under the influence of drugs, there is an incentive for improving oral fluid testing technique and methodology.…”
Section: Analysis and Detection Of Z-drugsmentioning
confidence: 99%
“…In addition, delta-9-tetrahydrocannabinol (THC) is frequently detected in the blood or saliva of impaired drivers suspicious of erratic driving or involved in road accidents [1,2]. Although urine and plasma are commonly utilized for cannabinoid testing, the acceptance of oral fluid as an alternative testing device matrix has increased in the past two decades [3]. Oral fluid is an attractive drug-testing tool because the procedure for obtaining the desired specimens is easier, safer and less invasive as compared to urine and plasma.…”
Section: Introductionmentioning
confidence: 99%